VD_FINDINFO Pron / 2011 / 49 vom 24. Juni 2011 - VD Tribunal cantonal (2011)
EXPULSION DE LOCATAIRE, EXÉCUTION FORCÉE, PROCÈS DEVENU SANS OBJET | 309 let. a CPC (CH), 319 let. a CPC (CH), 321 CPC (CH), 326 al. 1 CPC (CH), 339 al. 2 CPC (CH), 405 al. 1 CPC (CH)